1994
DOI: 10.1016/0014-5793(94)00387-4
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's β‐amyloid peptide specifically interacts with and is degraded by insulin degrading enzyme

Abstract: Cerebral deposition of B-amyloid peptide @A) is a hallmark of Alzheimer's disease. Concentration of /IA could play a critical role in the rate of amyloid deposition. It is therefore of considerable importance to identify proteases involved in processing ofpA. '251-labeled synthetic /IA specifically cross-linked to a single protein with M, = 110,000 in cytosol fractions from rat brain and liver. This protein was identified as insulin degrading enzyme (IDE) since the labeling of the 110 kDa protein was completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
279
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(286 citation statements)
references
References 31 publications
3
279
0
4
Order By: Relevance
“…It is also interesting to outline that if we compare these parameters with those obtained for the amyloid peptides Aβ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and Aβ [16][17][18][19][20][21][22][23][24][25][26][27][28] several similarities and some differences emerge [54]. In particular, the overall proteolytic activity toward the main cleavage sites (i.e., Phe 24 [16][17][18][19][20][21][22][23][24][25][26][27][28] ) is somewhat higher in the case of the B20-30 peptide due to a slightly more efficient cleavage rate-limiting step (see Table 2), whereas the substrate affinity of B20-30 appears intermediate between that of Aβ [1][2][3]…”
Section: Effect Of Metal Ions On B(20-30) Processing By Idementioning
confidence: 99%
See 1 more Smart Citation
“…It is also interesting to outline that if we compare these parameters with those obtained for the amyloid peptides Aβ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and Aβ [16][17][18][19][20][21][22][23][24][25][26][27][28] several similarities and some differences emerge [54]. In particular, the overall proteolytic activity toward the main cleavage sites (i.e., Phe 24 [16][17][18][19][20][21][22][23][24][25][26][27][28] ) is somewhat higher in the case of the B20-30 peptide due to a slightly more efficient cleavage rate-limiting step (see Table 2), whereas the substrate affinity of B20-30 appears intermediate between that of Aβ [1][2][3]…”
Section: Effect Of Metal Ions On B(20-30) Processing By Idementioning
confidence: 99%
“…Since the discovery of insulin and Aβ cleavage by IDE [11], much effort has been put in trying to understand some key questions regarding cleavage sites [12,13], kinetics of substrate interaction [14,15] and the mechanism of IDE modulation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The brain possesses robust intrinsic Ab clearance mechanisms (Tanzi et al, 2004). Ab peptides are proteolytically degraded within the brain mainly by neprilysin (NEP) (Iwata et al, 2000) and insulin-degrading enzyme (IDE) (Kurochkin and Goto, 1994). It has been recently reported that ApoE facilitates the proteolytic clearance of soluble Ab from the brain both within microglia by NEP and extracellularly by IDE, in a process dependent on ApoE isoform and its lipidation level, where the cholesterol transporter ABCA1 and the nuclear liver X receptors (LXR) have a major role .…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest a role for both insulin-degrading enzyme and neprilysin (NEP) in the degradation of extracellular A␤ (3)(4)(5)(6)(7)(8)(9)(10). Matrix metalloproteinase-9, EC 3.4.24.15, and ␣ 2 -macroglobulin complexes have also been reported to play a role in A␤ degradation (11)(12)(13).…”
mentioning
confidence: 99%